Broadcast discussion on ?unemployment? - Lyon, Stanley; Glenavy, Lord; Johnson, Thomas; O Buachalla, Liam; Coyne, E. J. (Statistical and Social Inquiry Society of Ireland, 1940)
The first discussion by members of the Society, by way of broadcast, was on the population problem; the subject for this evening is "Unemployment." There is no necessity for me to enlarge on all that this single word connotes. In our discussion tonight we mean those who, being normally dependent on wage earnings, are genuinely seeking work and are unable to obtain it. The problem is one of long standing and affects the lives and happiness of a substantial section of the community. The backward or the less civilised countries of the world seem to have little unemployment as we know it. With them the standard of living is comparatively low whereas in what are regarded as the more advanced and highly civilised countries, in which there is a high standard of living, unemployment is a serious problem, the solution for which so far has been elusive. Agricultural countries seem to suffer less from its effects than industrial countries.
Broadcast on 9th May 1940
Keywords: Unemployment; Capitalism; 314.15